An integrated approach for warehouse design and planning - Pereira, Guilherme (2011)
Warehouse design and planning is a great challenge in the field of Supply Chain Management. Inventory level management, warehouse design and operations, and customers’ requirements are examples of important challenges in this context. Throughout this work we discuss a mathematical model aiming to support some warehouse management decisions and inventory decisions. Our aim is to show model’s potentialities and weaknesses when applied to real world problems and to identify challenging research opportunities for developing more global warehouse decision support models to fill the gap between researchers and warehouse practitioners.